SLA developmental stages and teachers' assessment of written French: Exploring Direkt Profil as a diagnostic assessment tool. (July 2014) - Granfeldt, Jonas; Ågren, Malin
One core area of research in Second Language Acquisition is the identification and definition of developmental stages in different L2s. For L2 French, Bartning and Schlyter (2004) presented a model of six morphosyntactic stages of development in the shape of grammatical profiles. The model formed the basis for the computer program Direkt Profil (Granfeldt et al., 2006), which carries out an automated analysis of the developmental stage of a learner text. The aim of the present study was to explore the relevance of Direkt Profil as a diagnostic assessment tool by comparing Direkt Profil's automated profile analysis with assessment by trained language teachers. Data for the present study come from the CEFLE corpus of written L2 French (Ågren, 2008). The learner texts were first analysed for developmental stage by the computer program Direkt Profil. In a second step, seven experienced language teachers of French assessed the same texts. The results indicated relatively high degrees of correlation and showed that the analysis of developmental stage by Direkt Profil could explain 73% of the variance in the teachers' mean assessments ( r 2 = 0.735). In addition, we concluded that the teachers were in agreement with each other and with the computer program when assessing texts at low and high proficiency levels respectively. The most important variation in the teachers' assessments was found in texts at intermediate levels, due to an inconsistent use of grammar and vocabulary. One of the advantages of using Direkt Profil as a diagnostic assessment tool is that it provides immediate and detailed feedback indicating how certain types of linguistic structures, correct or incorrect, are related to different stages of development.